Physicochemical Studies of Some Forest Soils Occurring in Topo Sequence of West Bengal - Dolui, A. K.; Boxi, R. N.; Banerjee, S. K. (Indian Forester, 1985)
The physiochemical characteristics of some lateritic soild under forest flossr in topo sequence of West Bengal were studied. The soils were then classified according to modern system of classification. The chemical composition of these soils has been influenced to a great extent by drainage condition, different transport of eroded material, leaching, translocation and redeposition of mobile soil constituents. Chemical composition of the soils indicates trend in laterisation process. Appreciable base status of the soils, however, goes to prove that weathering has not progress so far.